PENINGKATAN HASIL BELAJAR TEMATIK DENGAN MODEL PEMBELAJARAN EXAMPLE NON EXAMPLE DI KELAS IV SD N 223/II RANTAU EMBACANG MUARA BUNGO - F, Fauziah; Rahayu, Suci (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2023)
The results showed that there was an increase in thematic learning outcomes that were pursued through the example non example learning model. This research was conducted in two cycles. This is indicated by the increase in learning outcomes based on the teacher's observation sheet, namely in the first cycle the student observation results at the first meeting were 70.31%, the second meeting was 71.87%, the third meeting was 75% and already in the second meeting. categorized as good and in the second cycle the increase in the first meeting was 78.12%, the second meeting was 79.68%, the third meeting was 84.37% and was categorized as very good. Student observation sheets, namely in the first cycle the results of student observations at the first meeting were 60%, the second meeting was 71.66%, the third meeting was 75% and was categorized as good and in the second cycle the increase in the first meeting was 75%, the second meeting was 78.33%, the third meeting is 83.33% and has been categorized as very good. Completeness in the final test is the number of students who completed before the action as many as 15 students (60% of all students). After being given action. in the first cycle, the number of students who completed learning increased to 16 students (64% of all students), and in the second cycle the number of students who completed the study increased to 20 students (80% of all students). Based on the results of the research above, students must focus on the learning process using example non example, this is an alternative model that can be used by teachers in the learning process to be able to improve learning outcomes and student activity in the classroom.